Spritualitas dalam Kurikulum Madrasah Aliyah Nurul Ummah Yogyakarta - Siti Aminah; Sinta Rahmatil Fadhilah (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
The curriculum is one of the tools to achieve educational goals, and at the same time it is used as a guide in the implementation of the teaching and learning process at various types and levels of schools. The curriculum is the basis for reflecting the philosophy of a nation's view of life, it will be directed to where and how the life of this nation will be in the future, all of which are determined and described in an educational curriculum. Spiritual-based education is able to touch the innermost side of students, namely their hearts or hearts, so that students know and are aware that they were created by God, were born into the world with the task of worship, are able to live gratefully, love fellow humans and other creatures because of God alone, obey and diligent in worship, care for others, respect for parents and teachers. So this article will discuss values ​​and curriculum from the meaning, function, and development of values ​​and curriculum in education science. Regarding the curriculum in schools, the location in this mini research study is at MA Nurul Ummah. This article is a qualitative research. As for the results of his research, MA Nurul Ummah is currently implementing the 2013 curriculum. Authentic assessment in the 2013 curriculum includes attitudes, knowledge and skills competencies. The implementation of the 2013 curriculum currently divides attitude competence into two. The first is a spiritual attitude and the second is a social attitude. The violations that occurred at MA Nurul Ummah in general were not sharia-based or spiritual violations, but disciplinary violations, so the punishment given was an educational matter regarding the student's discipline and points were also given depending on the size of the violation.